Multivitamin Use Is Associated with Increased Micronutrient Intakes and Biomarkers and Decreased Prevalence of Inadequacies in Middle-Aged and Older Adults. (29th May 2020) - Wallace, Taylor; Frankenfeld, Cara; Frei, Balz; Shah, Alpa; Yu, Ching-Ray; Klinken, Jan-Willem van; Adeleke, Maryann
Abstract: Objectives: Micronutrient inadequacies are common in older adults. We sought to assess if multivitamin/multimineral supplement (MVM) use improved micronutrient intake and biomarker status among older adults enrolled in NHANES. Methods: The National Cancer Institute Method was used to estimate usual intakes of 18 micronutrients stratified by age and frequency of MVM use. Insufficiency and deficiency prevalence were evaluated using nutrient biomarkers. Results: Compared with food alone, MVM use was associated with higher nutrient intake and lower prevalence of inadequacies of almost all micronutrients exam- ined and improved nutrient biomarker status of folate, iodine, selenium, and vitamins B6, B12, and D. Regular MVM use (!16days/month) decreased the odds of clinical deficiency (defined by biomarker status) of vitamins B6 and D but increased the proportion exceeding the tolerable upper intake level of folic acid. Vitamin B6 deficiency in MVM non-users was common and increased with age. Conclusions: Recommending MVM in the middle-aged and older adult population in the US may help to ensure opti- mal long-term nutritional status and contribute to health maintenance. Funding Sources: GSK Consumer Healthcare.